Structural dynamic response of an unreinforced masonry house using non-destructive forced vibration - A.R., Abdul Karim; N. M., Sa’don; J. M., Ingham (Taylor & Francis Group, 2016)
The results of non-destructive forced vibration tests on a small-scale unreinforced masonry house with a flexible timber diaphragm are presented. The primary purpose of this study was to investigate the dynamic responses between the as-built and retrofitted structures. This includes assessment of diaphragm response, wall-diaphragm connection details, in-plane wall response, out-of-plane wall response, and the response of wall corners. The test protocols were designed to investigate two types of retrofit techniques consisting of a plywood-retrofit on the diaphragm, and a connection-retrofit between the wall and diaphragm. From the results, one can see that the natural frequency and mode shapes of the first translational mode were affected. The force transfer mechanism of the as-built structure was significantly improved after applying both retrofits whereas each technique shows distinctive enhancements on the structure overall response.